Overcoming Religious Illiteracy - Moore, D. author. aut Link
XVI, 226 p.
Keywords: In Overcoming Religious Illiteracy, Harvard professor and Phillips Academy teacher Diane L. Moore argues that though the United States is one of the most religiously diverse nations in the world, the vast majority of citizens are woefully ignorant about religion itself and the basic tenets of the world's major religious traditions. The consequences of this religious illiteracy are profound and include fueling the culture wars, curtailing historical understanding and promoting religious and racial bigotry. In this volume, Moore combines theory with practice to articulate how to incorporate the study of religion into the schools in ways that will invigorate classrooms and enhance democratic discourse in the public sphere.